?So what if ChatGPT wrote it?? Multidisciplinary perspectives on opportunities, challenges and implications of generative conversational AI for research, practice and policy - Dwivedi, Yogesh K (ELSEVIER SCI LTD, 2023)
10.1016/j.ijinfomgt.2023.102642